Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1111/j.1349-7006.1997.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4 Expression Is Associated with the Increased Sensitivity of Human Non‐small Cell Lung Cancer Cells to DNA Topoisomerase I Inhibitors

Abstract: Inactivation of p16INK4, an inhibitor of cyclin‐dependent kinases 4 (CDK4) and 6 (CDK6), may be essential for ontogenesis in non‐small cell lung cancer (NSCLC). We examined the sensitivity of two clones of P16INK4‐transfected NSCLC cell line with homozygous deletion of p16INK4, A549/pl6‐l and 2, to DNA topoisomerase I (topo I) inhibitors. A549/pl6‐l and ‐2 showed 7.7‐ and 9.1‐fold increases in sensitivity to CPT‐11 (11,7‐ethyl‐10‐[4‐(1‐piperidino)‐1‐piperidino]carbonyloxycamptothecin), respectively, compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Fukuoka et al 7 reported that transfection of p16/CDKN2 gene into human nonsmall lung cancer cells resulted in increased sensitivity to topoisomerase inhibitors, doxorubicin, mitomycin C and 5-fluorouracil. Sading et al 8 suggested that simultaneously transfected wild-type p16/CDKN2 gene and wild-type TP53 gene induce apoptotic tumor cell death cooperatively in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuoka et al 7 reported that transfection of p16/CDKN2 gene into human nonsmall lung cancer cells resulted in increased sensitivity to topoisomerase inhibitors, doxorubicin, mitomycin C and 5-fluorouracil. Sading et al 8 suggested that simultaneously transfected wild-type p16/CDKN2 gene and wild-type TP53 gene induce apoptotic tumor cell death cooperatively in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…4 The putative tumor-suppresser genes, p16/CDKN2 and p15/ MTS2, are known to be inactivated by deletion, mutation and hypermethylation in a variety of human tumors. 5,6 Since several studies indicate controversial impacts of the gene inactivation on in vitro sensitivity to chemotherapeutic agents including cisplatin, [7][8][9][10] its contribution to the drug-resistance phenotype in cancer patients is not well understood.…”
mentioning
confidence: 99%
“…The log of the normalized p21 mRNA levels was plotted against time following actinomycin D treatment. All the values are expressed relative to time 0 h, which was arbitrarily assigned the value of 1. this question (42). Two novel inhibitors of DNA MeTase that inhibit DNA MeTase by different mechanisms were used to increase the confidence that the effects observed were a consequence of DNA MeTase inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…A549 cells have been reported to have a homozygous deletion of CDKN2a (36). Therefore, we hypothesized that p21…”
Section: Dose-dependent Inhibition Of Cell Proliferation By 5-aza-mentioning
confidence: 99%